Association of atrial tachyarrhythmias with atrial septal defect, Ebstein''s anomaly and Fontan patients. (July 2011) - Loomba, Rohit S; Chandrasekar, Suraj; Sanan, Prateek; Shah, Parinda H; Arora, Rohit R
The number of adults with congenital heart disease is increasing as medical and surgical palliation for congenital heart lesions improves. With this comes long-term complications of congenital heart disease such as the increased risk of atrial tachyarrhythmias. Atrial septal defect, Ebstein''s anomaly and post-Fontan patient subsets are particularly important to focus on due to their unique characteristics and association with atrial tachyarrhythmias. Reviews, randomized controlled trials, and meta-analyses were obtained using electronic search strategies such as Medline and the Cochrane Library. References of electronically obtained studies were then used to obtain additional relevant studies. Sources were deemed relevant if they discussed the relationship between atrial septal defects/Ebstein''s anomaly/Fontan procedure and atrial tachyarrhythmias in respect to incidence, mechanism, recurrence or treatment. Selected sources were then stratified on the basis of quality. Patients in these subsets of congenital heart disease are at increased risk of atrial tachyarrhythmias for a variety of reasons when compared with the general population. It is necessary for pediatric and adult cardiologists alike to understand these differences, as well as their implications in diagnosis and management of such occurrences.